2019
DOI: 10.1111/jfbc.12778
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of saflufenacil and three metabolites in five agriculture products using liquid chromatography—Tandem mass spectrometry

Abstract: A reliable and efficient method was firstly established for the simultaneous determination of saflufenacil and its metabolites (M800H02, M800H11 and M800H35) in cereals (soybean and corn) and fruits (apple, grape and orange), based on a triple quadrupole liquid chromatography mass spectrometer. The four target compounds were extracted with acetonitrile and purified by Florisil or Florisil with octadecylsilane from the cereals and fruits. Determination of the targets was achieved within 3.5 min by using Shim‐pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…For sediment samples the percentage of recovery was determined to be 85 ± 6% ( n = 8) with a method detection limit of 5.68 ng/tube (3σ/m, n = 5). This simple extraction method, which has proved to be effective in the extraction of saflufenacil from soils, requires less time and fewer materials than other published methods for saflufenacil extraction, allowing for more samples to be processed in a shorter time with equivalent recovery and detection limits (Lan et al 2014; Wu et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sediment samples the percentage of recovery was determined to be 85 ± 6% ( n = 8) with a method detection limit of 5.68 ng/tube (3σ/m, n = 5). This simple extraction method, which has proved to be effective in the extraction of saflufenacil from soils, requires less time and fewer materials than other published methods for saflufenacil extraction, allowing for more samples to be processed in a shorter time with equivalent recovery and detection limits (Lan et al 2014; Wu et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…There is limited peer‐reviewed literature regarding the monitoring for transport or persistence in soils from fields where saflufenacil has been applied, a fact noted in the most recent Canadian registration decision for saflufenacil (Health Canada 2017). In one of the most recent studies (Wu et al 2019), the authors identified a new analytical methodology to detect saflufenacil and 3 metabolites in consumer agricultural products. In an earlier study, Lan et al (2014) employed an analytical extraction method to detect saflufenacil and 2 metabolites in soil samples.…”
Section: Introductionmentioning
confidence: 99%
“…Under the optimal conditions, this method achieved recoveries of 76%-97% with RSDs of 1%-9%, low LODs (0.001-41.27 ng/L), and good linearity. Wu et al (2019) established an efficient method for analyzing saflufenacil and the metabolites simultaneously in agriculture products with LC-MS/MS. The sample extraction was carried out using acetonitrile, followed by purification with Florisil or Florisil with octadecylsilane, prior to detection with Shim-pack GIST C18 column connected to an EI source.…”
Section: Annual Literature Reviewmentioning
confidence: 99%